1997
DOI: 10.1016/s0893-133x(97)00089-4
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Striatal 6-FDOPA Uptake with Increasing Duration of Cocaine Withdrawal

Abstract: It has been hypothesized that a decrease in dopaminergic presynaptic activity during abstinence or withdrawal is related to relapse in cocaine-dependent subjects (Dackis and Gold 1985;Markou and Koob 1991). This study measured striatal Cocaine is one of the most potent and reinforcing central nervous system stimulants (Withers et al. 1995). Cocaine's pharmacological effects are due to its binding of the dopamine transporter molecule, thereby increasing intrasynaptic dopamine concentration (Giros et al. 1996)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
52
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 38 publications
(39 reference statements)
7
52
0
1
Order By: Relevance
“…In cocaine addiction, PET imaging with [ 18 F] dopa (6-[ 18 F] fluoro-L-dopa) shows a delayed decrease in DA terminal activity in the striatum of detoxified cocaine abusers compared with controls [34,35] . Also, a decrease in presynaptic DA activity during cocaine abstinence or withdrawal is associated with relapse [36,37] .…”
Section: Pet Studies Of Presynaptic Da Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…In cocaine addiction, PET imaging with [ 18 F] dopa (6-[ 18 F] fluoro-L-dopa) shows a delayed decrease in DA terminal activity in the striatum of detoxified cocaine abusers compared with controls [34,35] . Also, a decrease in presynaptic DA activity during cocaine abstinence or withdrawal is associated with relapse [36,37] .…”
Section: Pet Studies Of Presynaptic Da Synthesismentioning
confidence: 99%
“…Uptake of L-dopa labeled with a positron-emitting radionuclide refl ects the synthesis rate of DA in the terminals, under the conditions of PET [32,33] . Studies with PET and radionuclidelabeled L-dopa and their main fi ndings are summarized in [34,35] . Also, a decrease in presynaptic DA activity during cocaine abstinence or withdrawal is associated with relapse [36,37] .…”
mentioning
confidence: 99%
“…It has been showed that a decrease in dopaminergic presynaptic activity during abstinence or withdrawal is related to relapse in cocaine-dependent subjects (Dackis and Gold, 1985;Markou and Koob, 1991). PET imaging with [ 18 F] dopa has found in the detoxified cocaine abusers a delayed decrease in DA terminal activity in the striatum compared with controls (Bell et al, 1996;Wu et al, 1997).In the study of Heinz et al (2005), although no difference of striatal [ 18 F] dopa net influx, an index of DA synthesis capacity, was found between detoxified alcoholic patients and the control subjects, the results showed that a low DA synthesis capacity correlated with alcohol craving which was associated with a high relapse risk.…”
Section: Assessment Of Presynaptic Da Synthesis and Dat Of The Dopamimentioning
confidence: 87%
“…A recent article in Neuropsychopharmacology (Wu et al 1997) reports the first attempt to assess with positron emission tomography (PET) the effects of chronic cocaine use on the cerebral influx of 6-[ 18 F]fluoro-L-DOPA (FDOPA), a tracer for DOPA decarboxylase in catecholamine fibers of living human brain. Other PET studies have probed the occupancy of dopamine uptake sites or post-synaptic receptors in cocaine users (Volkow et al 1996(Volkow et al , 1997.…”
mentioning
confidence: 99%
“…The magnitude of K i is then estimated from linear regression of this distribution volume as a function of the normalized and metabolite-corrected integral of FDOPA in arterial plasma (Martin et al 1989). Wu et al (1997) employ an ingenious method for defining contiguous regions in brain for statistical comparisons of K i between subject groups, and for comparing effects of acute and chronic withdrawal from cocaine. However, it is not revealed how regions of interest (Figure 2) or reference regions in brain were delineated, nor is it explained how the HPLC fractionation of tracers in arterial plasma was accomplished.…”
mentioning
confidence: 99%